Incidence of Extended-Spectrum Î²-lactamases ESBLs producing Escherichia coli in patients with urinary tract infection - Abd, Firas Srhan; Almohana, Ali Muhsin (Al-Qadisiyah Journal of Pure Science, 2017)
Two hundred seven isolates of Escherichia coli were isolated from urine samples collected from patient suffering from UTI obtained from Al-Diwaniya Teaching Hospital. During the period from March 2011 to May 2012, a total of 2000 urine samples were collected from patients with suspected UTI. Identification according to the traditional biochemical tests, then confirmed by VITEK 2 system. Detection of ESBLs by using initial screening and confirmatory test which carry out by disk approximation or double disk synergy test (DDS) and CHROMagar methods, showed that 186 (89.8%) / 207(100%) of E. coli were initially screened as positive for ESBL. CHROMagar CTX technique was the most 166 (80.2%) ambient method than the disk approximation or (DDS) 0(0.0%) tests regarding confirmation of ESBL production. The results revealed that Screening and confirmatory tests considered the most accurate method for detection of ESBL- producing isolates, while the disk approximation was not accurate method in detecting such enzymes. The results of PCR assay showed that, 50 (100%) and 49 (98.0%) of the blaCTX-M positive isolates harbored blaSHV and blaOXA genes, respectively. While, blaTEM, blaPER, blaVEB and blaGES genes were not detected in this investigation.